[Laiškas] / Vanagas Petras, kunigas - Tadui Vrublevskiui. - (:unkn) unknown (My University, 1908)
1 laiškas apie siunčiamus dokumentus ir konsultaciją dėl bylos.
Keywords: Rankraščiai; Laiškai; Autografų kolekcija; Vanagas, Petras, 1874-1949; Vrublevskis, Tadas Stanislovas, 1858-1925